Rewizja idei repatriacji w świetle postulatu Marcusa Garveya i postkolonialnych transformacji - Lipiński, Kamil (Człowiek i Społeczeństwo, 2014)
The paper examines the transformations of the idea of repatriation raised by Marcus Garvey’s postulate and which subsequently emerged from the Rastafari movement and developed within reggae and dub lyrics. The mentioned idea has been analyzed in terms of widespread undergoing processes of its dissemination within glocal diasporas and the creation of post-colonial mimicry. Drawing on the so called doctrine of “ethiopianism” described by Marcus Garvey as a return to the “promised land” in the aftermath of the coronation of Haile Selassie I for the King of Ethiopia, it became the main leading concept in the settlement of the “Pinnacle” enclave in the early 1930s. By spreading consequently this directive within two waves of persecution and re-settlement of the movement in the downtown area of Kingston in the early 1950s, it stimulated the emergence of entrepreneurship and the organization of the urban Sound Systems designed for the lowest social class and triggered the development of its doctrine in the vast array of lyrical forms. These premises of anti-colonial liberation and the improvement of life conditions were initially articulated in the form of a native, Jamaican, creolized “patois” dialect, i.e. by Louise Bennett and subsequently by reggae artists, as well as “dub poets”, such as Linton Kwesi Johnson, Oku Onuora, and Mutabaruka. As a result of the dispersion of the idea within glocal diasporas, it was gradually in-rooted into music genres and proliferated within a diversified industry. Thus, the unfinished project of utopian return has been rearticulated in the stratified distribution market, gaining a trans-local revival thanks to the ability of its transformation within new industrial conditions.